Analysis of The Influence of Technology Perceived Quality, Digital Advertising and Technology Digital Experiental Marketing on Customers Intention to Purchase at Marketplace Platform Tokopedia - Sudirjo, Frans; Nurbakti, Rezky; Hadi Nugroho, Isfauzi; Ekaputra, Adriansyah; Yuniarti Utami, Eva (Jurnal Informasi dan Teknologi, 2023)
The study's goal is to examine how advertising, perceived quality, and experiential marketing affect consumers' decisions to buy. The judgment sampling approach is the sample technique employed in this study. Based on the assumption that respondents had shopped online, samples were chosen. One hundred samples will be collected for this study. In this study, the author employed two different types of data: primary and secondary. Using Cronbach's alpha, researchers assess a variable's dependability in this test. Multiple linear regression analyses are used in the examination of research data. Experience marketing, perceived quality, and advertising are found to have a major impact on the purchasing decisions of customers who actively use e-commerce applications, according to the research findings. The a-value of 13.4 shows the buyer's decision value when there is no influence from the experiential marketing, perceived quality, or advertising variables. The regression coefficients b1, b2, and b3 each show that a one-unit increase in the experiential marketing, perceived quality, and advertising variables will result in an increase in purchasing decisions by 0.24, 0.2, and 0.24 respectively.